A Winkler-based model for inelastic response of soil–structure systems with embedded foundation considering kinematic and inertial interaction effects. (December 2020) - Asadi-Ghoozhdi, Hamid; Attarnejad, Reza
Abstract: In this paper, a parametric study is carried out on the ductility and displacement demands of structures with embedded foundation considering nonlinear soil–structure interaction (SSI). The soil–embedded foundation interaction is simulated using the beam on Winkler foundation concept. The bilinear behavior is also assumed for the equivalent single-degree-of-freedom (SDOF) structure. Effect of key parameters including fundamental period, level of inelasticity, soil flexibility, embedment ratio, and slenderness ratio on the seismic demands is examined. A family of soil–structure systems are analyzed subjected to a group of 33 ground motions recorded on alluvium deposits. Both sway and rocking components of foundation input motion are applied to the system. Results reveal that foundation embedment generally increases the ductility demand of the SDOF system. Moreover, the kinematic interaction (KI) effect on ductility demands is more prominent for structures with deep embedment ratios. As the aspect ratio increases, the role of rocking input motion on ductility and displacement demands becomes more noticeable. It is also concluded that the nonlinear SSI can increase the displacement demand of interacting systems as compared to the equivalent linear soil model. Based on the obtained results, a simplified expression is proposed to estimate the displacement ratio for soil–structure systems with embedded foundation considering KI effects.